Secure lightweight pairing-based key-agreement cryptosystems: issues and challenges - Ghoreishi, Seyed Mohsen (2013)
Although a large number of pairing-based key-agreement cryptosystems have been proposed, there are still a lot of drawbacks. One of the most important disadvantages of mentioned cryptographic functions is that there is not a comprehensive system to satisfy both security and efficiency requirements. Moreover, there is not an integrated document to categorize and present possible challenges. Therefore, we paid particular attention to this issue, unlike other surveys in the area of key-agreement cryptosystems. In this paper, we presented a new method to address possible challenges. Actually, we claim that unlike existing documents, this paper determines possible challenges and open problems in the area of lightweight pairing-based key-agreement cryptosystems. We expect that our findings make other researchers able to classify all presented cryptosystems in this area and help them to follow the best way to solve possible problems in the future researches.